2019
DOI: 10.1111/jdv.15907
|View full text |Cite
|
Sign up to set email alerts
|

Basal cell carcinoma treated with combined ablative fractional laser and ingenol mebutate – an exploratory study monitored by optical coherence tomography and reflectance confocal microscopy

Abstract: Background Basal cell carcinomas (BCCs) have previously been treated off‐label with ingenol mebutate (IM). Ablative fractional laser (AFL) may improve efficacy of IM by increasing drug uptake in the tumour. Optical coherence tomography (OCT) and reflectance confocal microscopy (RCM) detect BCC non‐invasively. Our aim was to investigate BCC response and tolerability after combined AFL and IM treatment of low‐risk BCCs. Methods Twenty patients with histologically verified superficial (n = 7) and nodular (n = 13)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 30 publications
(77 reference statements)
3
14
0
Order By: Relevance
“…Persisting erythema, here observed in 83% of patients, also appears common after AFL-assisted topical BCC therapy, with reported rates of 74% (4-8 weeks) and 73% (3 months) using 5-FU and PDT, respectively [45,46]. In regard to hyperpigmentation (57%), our rates were similar to Choi et al [41] (67%; AFL + PDT) and Banzhaf et al [43] (64%) who assessed at similar follow-up times, but higher than reported by Nguyen et al [45] (30%; AFL + 5-FU) and Genouw et al [40] (20%; AFL + PDT). These differences may reflect variations in laser settings or tumor location.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Persisting erythema, here observed in 83% of patients, also appears common after AFL-assisted topical BCC therapy, with reported rates of 74% (4-8 weeks) and 73% (3 months) using 5-FU and PDT, respectively [45,46]. In regard to hyperpigmentation (57%), our rates were similar to Choi et al [41] (67%; AFL + PDT) and Banzhaf et al [43] (64%) who assessed at similar follow-up times, but higher than reported by Nguyen et al [45] (30%; AFL + 5-FU) and Genouw et al [40] (20%; AFL + PDT). These differences may reflect variations in laser settings or tumor location.…”
Section: Discussionsupporting
confidence: 89%
“…The bulk of these reports assess AFL-photodynamic therapy, where clearance rates of 100% (sBCC), 79% (nBCC; <2 mm thick) and 63% (nBCC; high risk) are reported 12 months after 1-2 treatments [40][41][42]. Two studies also evaluate AFL-assisted imiquimod and ingenol mebutate, observing clearance in 78% (FU: 20 days) and 70% (FU: 90 days) of sBCC and mixed tumors, respectively [43,44]. Resembling our study, Hsu et al showed that a single session of AFL-assisted 5-FU cleared 71% of sBCCs at 4-8 weeks (10/14; <20 mm), dropping to 67% at >9 months follow-up [45,46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Reflectance confocal microscopy (RCM) and optical coherence tomography (OCT) are non-invasive optical imaging technologies capable of visualizing the cutaneous micromorphological response to a range of treatments in vivo. [26][27][28] Evidence on the clinical utility of RCM and OCT for diagnosis of dermatological conditions and monitoring treatment responses is growing rapidly. 29 Recent reports on the high correlation between clinical acne severity and optical imaging features substantiated the utility of non-invasive imaging.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of differentiating benign skin lesions from malignant ones has in the recent years been overcome by advances in several non‐invasive optical imaging techniques 8 . In this study, we applied the three clinically most promising and relevant technologies: reflectance confocal microscopy (RCM) that provides cellular resolution and micro‐morphological information of skin disease, useful for diagnosis of BCC subtypes, MM and lentigo maligna, 9,10 to determine pre‐surgical margins for melanocytic lesions and keratinocyte carcinomas, 10,11 to monitor therapeutic interventions of skin cancers and various inflammatory skin diseases 12‐15 . By illuminating the skin with near‐infrared lasers, RCM creates images by light energy being absorbed and reflected depending on the refractive index of the structure of interest 9 .…”
Section: Introductionmentioning
confidence: 99%